The Potential for Blockchain Technologies in the Mining Industry - Anderson, Sakshi; Barakos, George (SDIMI, 2024)
The mining industry is well-versed with smart technology and has leveraged its benefits for decades. As the technology has evolved, it has been tested and deployed in the mining industry to optimize the process chain. The mining industry also operates within disparate global landscapes marred by human rights violations, concerns around child labour, and conflict minerals (Bebbington and Bebbington, 2018). In recent years, these challenges have led to the emergence of provenance, traceability, and transparency as key aspects of sustainable mining and have resulted in a ‘new political economy of mineral extraction’ (Seagle 2012). The principles of sustainability and transparency are linked with conservation, life-cycle analysis and digitization, and other aspects of ‘extractivism’ (Calvão and Archer 2021). Governments in Europe, North America, Africa, and Oceania are looking to blockchain and related technologies to provide transparency and traceability across a complex mining value chain. These technologies present opportunities and challenges for a global mining industry faced with everevolving geopolitics as the globe sets its sights on energy transition, carbon neutrality, and sustainability in the coming decades. This paper seeks to outline these opportunities and challenges and presents a case for industry-government partnerships in forging new institutional structures supporting transparency and traceability in coming years.